The Effects of a Weighted Football Intervention on Ball Velocity of a Standard Football Place-Kick among Elite Gaelic Football Goalkeepers: A Single-Subject Designed Study - Sam Jermyn; Cian O’Neill; Seán Lacey; Edward K. Coughlan (Sports, 2022)
Weighted football place-kicking acutely enhances the ball velocity (BV) of subsequent standard football place-kicks. However, there is a dearth of research examining the long-term effects of such interventions, with less evidence in existence among elite athlete cohorts. Therefore, the purpose of this study was to investigate the individual effects of a 4 week, eight-session weighted Gaelic football intervention on BV of standard Gaelic football place-kicks among six elite male Gaelic football goalkeepers. This research design was based on a pre-, mid-, post-, and retention-test design. A linear mixed model analysis was employed, with time and participants as fixed effects, and the number of place-kicks per testing session as a random effect. Post hoc tests revealed significant changes in BV for five of the six participants (p < 0.05), with three participants experiencing significant BV increases from pre-test to post-test (p < 0.05), while no significant differences were found between post-test and retention-test. The remaining three participants experienced no significant BV differences from pre-test to post-test and retention-test. These findings suggest that a weighted football place-kicking intervention can be a time-efficient means of maintaining and enhancing BV and, thus, kick distance, among elite goalkeepers during pre-season and in-season phases.